Selective light driven reduction of CO2 to HCOOH in water using a MoV9n (n = 1332–3600) based soft-oxometalate (SOM). Issue 19 (16th February 2018) - Barman, Soumitra; Das, Santu; S. S., Sreejith; Garai, Somnath; Pochamoni, Ramudu; Roy, Soumyajit
Abstract : A soft-oxometalate (SOM) based on Mo and V i.e. MoV9 in their highest oxidation state reduces CO2 to HCOOH selectively in water. Abstract : A soft-oxometalate (SOM) based on Mo and V i.e. MoV9 in their highest oxidation state reduces CO2 to HCOOH selectively in water. Catalysis initiates without the use of any photosensitizer and solvent water acts as the sacrificial electron donor which gets oxidized to generate oxygen. Electrons and protons released in this process reduce CO2 to HCOOH.